2022
DOI: 10.1038/s41467-022-31929-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential neutralization and inhibition of SARS-CoV-2 variants by antibodies elicited by COVID-19 mRNA vaccines

Abstract: The evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in the emergence of new variant lineages that have exacerbated the COVID-19 pandemic. Some of those variants were designated as variants of concern/interest (VOC/VOI) by national or international authorities based on many factors including their potential impact on vaccine-mediated protection from disease. To ascertain and rank the risk of VOCs and VOIs, we analyze the ability of 14 variants (614G, Alpha, Beta, Gamma, De… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Omicron variants, including the recently emerged variants BA.4 and BA.5, which are more infectious than the original WA1 strain, are spreading throughout the globe since late 2021 [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Both primary and booster vaccinations produce low protection against Omicron variants compared to WA1 strain and initial SARS-CoV-2 variants [ 21 , 22 , 23 ]. Thus, the Omicron variants partially escape from the WA-1 induced neutralization [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Omicron variants, including the recently emerged variants BA.4 and BA.5, which are more infectious than the original WA1 strain, are spreading throughout the globe since late 2021 [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Both primary and booster vaccinations produce low protection against Omicron variants compared to WA1 strain and initial SARS-CoV-2 variants [ 21 , 22 , 23 ]. Thus, the Omicron variants partially escape from the WA-1 induced neutralization [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Over the course of the pandemic, however, new SARS-CoV-2 variants have continued to emerge and evade vaccine-induced immunity. 2 Following a Delta variant predominant period, the Omicron BA.1 sublineage became predominant in the United States by December 2021. Compared to earlier SARS-CoV-2 variants, BA.1 demonstrated increased transmissibility and immune evasion with a reduction in vaccine effectiveness (VE) offset by COVID-19 vaccine booster doses.…”
Section: Introductionmentioning
confidence: 99%
“…The continued emergence of SARS-CoV-2 variants has raised concern that vaccines based on the Wuhan strain will exhibit reduced efficacy over time in the face of viral evolution 14 . This fear is further exacerbated in vulnerable populations among which vaccine effectiveness is already reduced 59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…Notable SARS-CoV-2 variants have arisen and expanded across the globe, including Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1), Delta (B.1.617.2), and most recently Omicron (B.1.1.529). While vaccination is a critical intervention in combatting the pandemic, many studies of both infection and vaccination have shown reduced neutralizing potency toward variants of concern (VOC) [4][5][6][7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%